Development of a single-tube one-step RT-LAMP assay to detect the Chikungunya virus genome - Lopez-Jimena, Benjamin; Wehner, Stefanie; Harold, Graham; Bakheit, Mohammed; Frischmann, Sieghard; Bekaert, Michaël; Faye, Oumar; Sall, Amadou Alpha; Weidmann, Manfred (PLoS neglected tropical diseases, 2018)
A single-tube one-step real-time reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay for rapid detection of chikungunya virus (CHIKV) targeting the conserved 6K-E1 target region was developed. The assay was validated with sera collected from a CHIKV outbreak in Senegal in 2015. A novel design approach by combining Principal Component Analysis and phylogenetic analysis of 110 available CHIKV sequences and the LAMP oligonucleotide design software LAVA was used. The assay was evaluated with an External Quality Assessment panel from the European Network for Diagnostics of "Imported" Viral Diseases and was shown to be sensitive and specific and did not cross-detect other arboviruses. The limit of detection as determined by probit analysis, was 163 molecules, and 100% reproducibility in the assays was obtained for 103 molecules (7/8 repetitions were positive for 102 molecules). The assay was validated using 35 RNA samples extracted from sera, and results were compared with those obtained by quantitative RT-PCR carried out at the Institut Pasteur Dakar, demonstrating that the RT-LAMP is 100% sensitive and 80% specific, with a positive predictive value of 97% and negative predictive value of 100%. The RT-LAMP appeared to show superior performance with material stored for months compared to qRT-PCR and can be therefore recommended for use in infrastructures with poor settings.